Corporate Governance Mechanism on Financial Performance (Evidence from the Indonesia’s Listed State-owned Enterprises) - Maldini, Anak Agung Kompiyang Ratih; Pasaribu, Pananda; Pangaribuan, Christian Haposan (APPS Publications, 2021)
Objective – This study aims to find the impact of privatization, which proxied by good corporate governance toward the financial performance of SOEs in Indonesia. Methodology – This study used 16 privatized SOEs that are listed in Indonesia Stock Exchange and also 16 privatized non-SOEs as the comparison. The data is collected from the year 2014 to 2018 and analyzed by using multiple regression panel data. Findings – This study found that director size and board independence have a positive impact toward SOEs financial performance. The director size and board independences have a positive significant impact toward the SOEs financial performance while the privatized non-SOEs is not significantly affected Novelty – This study examines proper governance structure in SOEs and non-SOEs, thus providing new insights about good corporate governance regulation in the Indonesian context.